Um olhar sensível e político sobre espaço de leitura: estudo de caso a partir do Literatório - Prado, Ana Paula do (Universidade do Vale do Rio dos Sinos, 2010)
Having as main focus issues involving the child and her possibilities concerning reading experiences, the work was produced from the accompaniment of experiments developed in the Literatório (Chapecó/SC) - a project that unites in the same space literature and enchantment. The text first presents reflections on the history of childhood, as well as about the importance of the practice of telling stories to child audience. The methodological option was based on "case study", drawing on in loco observations, and interviews with children and teachers of the first year of elementary school. In addition, interviews with subjects involved in the creation and management of the Literatório. The results allow verifying that such a move certainly has been developing the taste for literature among the children who attend it, with visible effects perceived by the teachers in the classroom. However, its coverage is still limited, demanding public policies that allow such possibilities to expand for a bigger number of children, and even to the population in general.
Keywords: Infância; Liberatório; Contação de histórias; Estudo de caso; Childhood; Storytelling; Case study; ACCNPQ::Ciências Humanas::Educação